2015
DOI: 10.1093/ofid/ofu119
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Regimen and Suboptimal Medication Adherence Are Associated With Low-Level Human Immunodeficiency Virus Viremia

Abstract: Episodes of human immunodeficiency virus low-level viremia (LLV) are common in the clinical setting, but its association with antiretroviral therapy (ART) regimen and adherence remains unclear. Antiretroviral therapy adherence was evaluated in participants of the Research on Access to Care in the Homeless cohort by unannounced pill counts. Factors associated with increased risk of LLV include treatment with a protease inhibitor (PI)-based regimen (ritonavir-boosted PI vs nonnucleoside reverse-transcriptase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 15 publications
1
21
2
Order By: Relevance
“…While reasons for ART switch were not available, plasma VL, duration of HIV infection, and nadir CD4 count were adjusted for in analyses, and the follow-up period was restricted to visits with plasma VL <1000 copies/mL on consecutive visits to reduce biases that result from virological failure. ART adherence is a critical factor in maintaining durable viral suppression [ 37 ] and could not be fully assessed due to missing data at the time of CSF escape. However, subanalyses of visits with suppressed plasma VL as a proxy for ART suppression showed that PI use remained an independent predictor of CSF escape.…”
Section: Discussionmentioning
confidence: 99%
“…While reasons for ART switch were not available, plasma VL, duration of HIV infection, and nadir CD4 count were adjusted for in analyses, and the follow-up period was restricted to visits with plasma VL <1000 copies/mL on consecutive visits to reduce biases that result from virological failure. ART adherence is a critical factor in maintaining durable viral suppression [ 37 ] and could not be fully assessed due to missing data at the time of CSF escape. However, subanalyses of visits with suppressed plasma VL as a proxy for ART suppression showed that PI use remained an independent predictor of CSF escape.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma antiretroviral concentrations have infrequently been assessed in conjunction with LLV [ 3 , 34 , 36 , 46 ]. In agreement with our study, most LLV are not associated with decreased antiretroviral concentrations [ 3 , 34 , 36 ], although in one study, a sensitivity analysis found a modest association [ 46 ]. Co-administration of rifampin and NVP can diminish NVP concentrations because of activation of hepatic enzymes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite increasing access to ART, several studies in Thailand and worldwide have found decreased adherence and rebound in mortality in adolescents receiving ART as compared to adults and young children[ 3 5 ], with poorer adherence when children advance in age[ 6 8 ]. Good adherence to the ART is crucial for successful viral suppression, as incomplete adherence leads to an increase in HIV viremia, risk of treatment failure, and accumulating resistance mutations[ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%